Neuroendocrine-immune relationships at rats regardless of sex and exposure to stressors or adaptogens - Plyska, Oleksandr; Vorobienko, Alyona; Yanchii, Roman; Żukow, Xawery (Journal of Education, Health and Sport, 2023)
Introduction and aim. Since the discovery of the famous Selye triad, studies of the connections between adaptation hormones and the immune system have remained relevant. We formulated the aim of the future study: in the mode of synchronicity, to reveal sexual differences in the parameters of the neuroendocrine-immune complex and the state of neuroendocrine-immune relationships in intact rats and exposed to stressors and adaptogens. This article initiates the beginning of the movement towards achieving the goal. Material and methods. The experiment is at 96 rats Wistar line: 48 males and 48 females. Over the 12 days, one male and female rat remained intact and 3 other pairs were exposed to chronic aversive stress for 6 days. We calculated the parameters of the HRV: Mode, Amplitude of the mode and Variational scope as markers of the circulating catecholamines, sympathetic and vagal tones respectively. Among endocrine parameters determined excretion of 17-Ketosteroides and serum levels of main adaptation hormones such as Corticosterone, Aldosterone, Testosterone, Triiodothyronine, as well as Parathyroid hormone and Calcitonin. The percentage of lymphocyte populations and the parameters of phagocytosis by neutrophils and monocytes of Staphylococcus aureus were determined in the blood. The Thymus and Spleen were weighed and made smears-imprints for counting Thymocytogram and Splenocytogram. Results. The canonical correlation between neuroendocrine and immune parameters was analyzed. The most pronounced immunomodulatory effect is exerted by catecholamines (R=0.928), sympathetic tone (R=0.849), and testosterone (R=0.829). Vagal tone (R=0.697), 17-ketosteroides (R=0.688), and aldosterone (R=0.686) moderately modulate immunity, while the immunomodulatory effects of triiodothyronine (R=0.610), corticosterone (R=0.584), PTH (R=0.510), and calcitonin (R=0.423) are the least pronounced. Three pairs of canonical roots were found. The neuroendocrine root of the first pair determines the parameters of immunity by 95.7%, the second pair by 86.5%, and the third pair by 69.2%. The elements of the Thymocytogram (in descending order: epitheliocytes, lymphocytes, endotheliocytes, lymphoblasts, and macrophages), the phagocytic activity of blood neutrophils and monocytes, the relative content of NK- and B-lymphocytes in the blood, as well as the percentage of lymphocytes and macrophages in the Splenocytogram turned out to be most influenced by neuroendocrine factors. Conclusion. There is a close canonical correlation between registered neuroendocrine factors and immunity parameters in general. At the same time, both the severity of the immunomodulatory activity of individual neuroendocrine factors and the subjection to the regulatory influence of individual parameters of immunity differ significantly.